Kristendom & sex - Den sexfjendtlige kristendom - Stender, Poul Joachim (Slagmark - Tidsskrift for idéhistorie, 2018)
For centuries Christianity has emerged as the most sex adverse religion on earth. However, it was not Jesus who made the world chaste. Indeed it was the world that made Jesus chaste. When reading the Bible it is obvious that the scriptures are anything but hostile towards sex. Eroticism is one of God’s great gifts to humankind. There is a connection between spirituality and sexuality. Both are part of a force that allows man to reach out – to reach beyond himself to make connections to and with others. Today sexuality is accepted as being created by God and Christianity is no longer hostile towards sexuality. Nonetheless, conservative Christians still lock up sexuality within the boundaries of lifelong heterosexual marriage, and liberal Christians do not discuss sexuality very often.